Feminizing the fetish : psychoanalysis and narrative obsession in turn-of-the-century France - Apter, Emily S., 1954- (Cornell University Press, 1991)
Emily Apter offers a fresh account of the complex relationship between representation and sexual obsession in turn-of-the-century French culture, and in particular the theme of ""female fetishism"" in the context of the feminine culture of mourning, collecting, and dressing